Arboviral diseases in Southern Africa - B. Prinsloo (South African Family Practice)
Arthropod-borne viral diseases, better known as arbovirus diseases, are more common than we think and are often misdiagnosed or not diagnosed at all. More than 100 arboviruses causing human disease have been recognised worldwide. This presentation will provide a review of some of the arboviruses occurring in Southern Africa, and also some of the common diseases seen in travellers returning home from other African and overseas destinations. The clinical syndromes vary extensively, with signs and symptoms ranging from acute benign fevers of short duration to the very dramatic viral haemorrhagic fevers. The reservoirs and vectors of most viruses are well described, but even after years of extensive research there are still a few that remain elusive and pose great challenges for future study.